Is firms' profitability affected by working capital management? A novel market-based evidence in Jordan - Mohammed Zakaria Soda; Mohammed Hassan Makhlouf; Yazan Oroud; Rania Al Omari (Cogent Business & Management, 2022)
This paper aimed to look into the relationship between working capital management and industrial firms' profitability listed on the Amman Stock Exchange (ASE) from 2014 to 2020. The data incorporated into the yearly statements of 23 listed industrial firms have been collated to investigate the developed model. In order to examine the data, pannel data procedure employed 161 observation. The empirical findings indicate that the working capital negatively influences the profitability of industrial companies in Jordan. Existing and potential financiers and stakeholders are incentivized to purchase more shares of quick conversion cash firms. More importantly, the study's findings provide practitioners with crucial financial insights and policy consequences. The combination is an important component that has directly and indirectly affected the financial status of the firm, which will eventually be reflected in its value. Current and potential investors shall evaluate the companies' total financial position rather than focusing on minor issues, such as payment days. This study contributes to the existing literature on the relationship between WCM and profitability of emerging market, and it's one of the few studies that investigate the elements of CCC individually and aggregated.
Keywords: D24; M41; P17; 650; cash conversion cycle; inventory days; Jordan; payable days; receivable days